Patterns of Language Maintenance and Use in the Family Environment in Negeri Wakasihu, Maluku - Erniati, Erniati; Wijaya, Dendi (Universitas Pendidikan Mandalika, 2023)
This research investigates the patterns of language use and maintenance of communities in Wakasihu State, Central Maluku, and highlights various factors that influence language maintenance. This research seeks to reveal the complexity of maintaining the use of regional languages inÂ Wakasihu State by looking at social variables such as age, gender, education and employment on language maintenance patterns. By using a quantitative descriptive approach enriched with mixed methods, this study combines the depth of qualitative insight with the breadth of quantitative data. Qualitative techniques, including observation, note-taking and interviews, provide a complex picture of the linguistic landscape of the Wakasihu community. To complement this, quantitative data was collected through a random questionnaire distributed to 50 communities. This questionnaire investigated the use of regional languages, their users, and how they are maintained. The findings of this study explain the dynamics of the use of interesting language in Wakasihu Country. Age is an important factor, the older generation shows a higher level of language retention. In contrast, the younger generation shows a lower level of retention of their local language. This generational shift signifies a change in the linguistic landscape in society. This study underscores the complex relationship between social dynamics, attitudes, and patterns of language use, offering a comprehensive understanding of how these factors influence language preservation and vitality. As the linguistic landscape develops, cultivating positive attitudes and awareness among the younger generation is essential for the survival of the Hitu dialect of the Wakasihu language. Moreover, the results of this research have implications not only for the Wakasihu community but also for similar linguistic contexts around the world, and constitute a strong call for proactive steps to safeguard our linguistic heritage.